Macrophage Activation - Biology and Disease 2020
DOI: 10.5772/intechopen.86433
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Regulates Macrophage Mediated Immune Response to Pathogens

Abstract: Infection with pathogenic microbes is a global threat. Macrophages play a fundamental role in promoting host resistance to deadly infections from pathogenic microbes by virtue of a well-orchestrated immune defense system. Phagocytosis and obliteration of invading pathogens by macrophages are an innate immune function that not only sustains immune homeostasis but also bolsters adaptive immune response through antigen processing and presentation. Wnt signaling, where Wnt, a secreted glycoprotein which interacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…In view of the role of Wnt5A signaling in actin assembly ( 16 , 24 , 27 , 28 ), we studied how the Wnt5A–Actin axis regulates the outcome of infection by a bacterial pathogen ( E. coli K1 isolate from a biliary sepsis patient) as compared to a non-pathogen (lab strain E. coli DH5α or E. coli K12-MG1655). The basis of pathogenicity and non-pathogenicity of these E. coli strains have already been documented ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the role of Wnt5A signaling in actin assembly ( 16 , 24 , 27 , 28 ), we studied how the Wnt5A–Actin axis regulates the outcome of infection by a bacterial pathogen ( E. coli K1 isolate from a biliary sepsis patient) as compared to a non-pathogen (lab strain E. coli DH5α or E. coli K12-MG1655). The basis of pathogenicity and non-pathogenicity of these E. coli strains have already been documented ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several labs including ours’ have demonstrated that Wnt5A signaling induces alterations in actin assembly in macrophages ( 16 , 24 , 27 , 28 ). This finding is in perfect agreement with the depicted role of Wnt5A in bacterial phagocytosis ( 15 ).…”
Section: Introductionmentioning
confidence: 93%
“…In light of the demonstrated association of actin dynamics with Wnt5A signaling ( 9 , 17 , 36 ), we investigated if Wnt5A-assisted survival of the commensal bacteria is linked with actin assembly. Indeed, Wnt5A depletion-induced reduction in E. faecalis and L. rhamnosus survival in macrophages was clearly associated with diminution in actin assembly as demonstrated by confocal microscopy and subsequent ImageJ (intensity) analysis of phalloidin-stained cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A Wnt5A-Actin axis supports the survival of commensal bacteria. In light of the demonstrated association of actin dynamics with Wnt5A signaling (9,17,32), we investigated if Wnt5A assisted survival of the commensal bacteria is linked with actin assembly. Indeed, Wnt5A depletion induced reduction in E. faecalis and L. rhamnosus survival in macrophages was clearly associated with diminution in actin assembly as demonstrated by confocal microscopy and subsequent ImageJ (intensity) analysis of phalloidin stained cells (Fig.…”
Section: Resultsmentioning
confidence: 99%